Pelaksanaan Pembelajaran Musik Ansambel Di Kelas X-2 SMA Negeri 1 Tilatang Kamang - Saidul Ihsan; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2022)
This study aims to determine how the implementation of learning in class X-2 SMA Negeri 1 Tilatang Kamang in arts and culture subjects using ensemble music material with Minangkabau songs. The type of research is qualitative research with a descriptive analysis approach and makes the researcher the main instrument in this research. To analyze the data, data collection, data reduction, data display and conclusion were drawn. The results showed that the process of implementing ensemble music learning in class X-2 SMA Negeri 1 Tialatang Kamang, was considered quite efficient due to complete facilities and students' willingness to learn well and try new things. In the implementation of learning is divided into 3 parts, namely, planning the teacher before carrying out learning activities, implementing practical learning activities, and evaluating the results of student training. The introduction of Minangkabau songs is done by using sheet music and with the direction of the teacher using the demonstration method.